Perivascular epithelioid cell tumour of the uterus: what do we know? - Wong, Yvonne W. Y.; Kang, Julian H. L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Perivascular epithelioid cell neoplasm (PEComa) is a rare mesenchymal tumour characterized by distinctive histological and immunohistochemical perivascular epithelioid cells. These tumours can be found in various anatomic sites, with gynaecologic PEComas accounting for nearly one-fourth of reported cases in the literature. However, due to its non-specific clinical presentation and a lack of definitive radiological appearance, the diagnosis of PEComas remains challenging. In this case report, we describe a 45-year old lady suffering from urinary retention secondary to large uterine fibroids, who then underwent a total hysterectomy. Postoperative histopathology with immunohistochemical stains confirmed an unexpected finding of uterine PEComa. Although the treatment of gynaecologic PEComas remains controversial, complete surgical resection with negative margins is recommended. A multidisciplinary approach will be beneficial in determining the necessity of adjuvant therapy such as targeted therapy with mTOR inhibitors, especially for PEComas which exhibit aggressive and high-risk features.